A rare case of isolated idiopathic gingival fibromatosis - Ashish Saini; Meghna Singh; Saimbi C Singh (Wolters Kluwer Medknow Publications, 2013)
Idiopathic gingival fibromatosis (IGF) is a rare condition. It is genetically heterogeneous and is usually part of a syndrome or, rarely, an isolated disorder. This study presents a rare case of 13 year old boy who was diagnosed with isolated IGF. This diagnosis has been based on clinical examination and after ruling out family, drug, and medical histories. External bevel gingivectomy has been done to remove excess gingival tissues. Excised tissue has been examined histologically. The patient has been followed up for a period of two and half years. No recurrence has been observed.